Republic of Korea : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that from 1999 to 2002, Korea's economy grew rapidly, by an average of 7u percent per year. But starting in 2003, the economy has begun to sputter. Growth suddenly stopped in the first half of the year, leapt ahead in the second half as exports boomed, but then slowed again to an anemic 2 3/4 percent annualized rate during January-September 2004 as exports decelerated. The authorities have been countering this slowdown by easing macroeconomic policies. The fiscal policy stance has been shifted from neutral to mildly expansionary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet